PENGARUH GOOD GOVERNANCE, GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI DAN PENGENDALIAN INTERN TERHADAP KINERJA PEMERINTAH DAERAH (Studi Empiris Pada SKPD Kota Pariaman) - Lestari, Yuni; Taufik, Taufeni; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to test the influence of good governance, leadership style, organizational commitment and internal control on performance of local government city of Pariaman. This research was carried out on the units of works devices of Pariaman. The population in this research is the employees who work in a work unit of the devices area, technique used is the sample of purposive sampling. The respondents in this study is the head of a work uji t the device area, the secretary of the working units of the device area, head of sub-division of finance and financial business unit of dresser’s official work of the device area. The sample used in this study as much as 76 respondents. Statistical methods are used to test the hyphothesis of the research is the analysis of multiple linear regression using the software SPSS version 21.00. Based on the calculation of the coefficient of determination (R2) obtained a value of 0,968. This show that the influence of the independent variables in the dependent 96,8% and the remaining 3,2% influenced by the other variables.Keywords: Good Governance, Leadership Style, Organizational Commitment, Internal Control and Local Government Performance.